The determinants of online hotel reservations among university staffs - Abu Bakar, Abdul Rahim; Hashim, Fariza (IBIMA Publishing, 2008)
To compete in the current business environment, hoteliers need to cut down their distribution costs and adopt the electronic distribution channels such as the Internet.However, Malaysian hotels have been relatively slow in adapting this due to the current preference of using traditional method of room reservation by hotel patrons. Based from the literature review of the Internet users, a public university was chosen to represent one of the profiles of Internet users.A sample of 193 respondents was collected and the findings indicated that profiles conformed to previous studies.In adopting online reservation, online “bookers” would look for fast, reliable and convenient system. Price is a key motivator to purchase online. The findings are important in encouraging more hoteliers to adopt and implement online hotel reservations as part of their main sales mechanism.